PENERAPAN TERAPI AKTIVITAS KELOMPOK BERMAIN KUARTET (KARTU) PADA PASIEN ISOLASI SOSIAL MENARIK DIRI - Riko Sandra Putra Riko; Diana H.Soebyakto (LPPM STIKes Mitra Adiguna, 2023)
Social isolation is an attempt to avoid interactions and relationships with other people. Patients who experience social isolation are characterized by flat affect, sad effects, wanting to be alone, inability to meet other people's expectations, and withdrawal. The purpose of this study was to find out the description of the application of Quartet Play Group Activity Therapy (cards) in social isolation patients withdrawing. The type of research used in this research is qualitative descriptive, namely in the form of research with a case study method or approach. The research results obtained based on the observation sheet assessed from the two clients showed that there was a difference where client I Mr.